Medición y control de nivel con aplicación a dspic - Abarca Coloma, Sebastián Humberto (2009)
The control of systems has evolved from a manual to an automatic status. In order to create an automatic control, a controller is needed to perform pre- established functions in an automatic to perform any desired processes. Electronics gives us solutions to develop automatic control systems using micro controllers. In this case, the problem is to control the liquid’s level according to the desired value using a digital signal controller “dcPIC’s”. The control process is made by acquiring the liquid’s level using a sensor. This value is then digitalized and linearized in order to be used in automatic control calculus. The desired value is imput trough a keyboard. The controller compares the actual measured value by the sensor and the imput reference value in order to perform the correction according to the existing error. The process of correction is performed trough the actuators which can be the pump or the electro valve depending on the error signal swing. A visualization of both the current liquid’s level and the imput reference value is also presented.